Investing in impacts to transform food systems in a changing climate: A design challenge for scaling sustainable finance in climate-smart agriculture - Koerner, Jana; Dinesh, Dhanush; Nagano, Akiko (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
An info note on a design challenge for scaling sustainable finance in climate-smart agriculture. In a virtual design thinking workshop (2nd semester 2020), representatives of the relevant financiers will design (elements) of these crucial mechanisms. Designing sustainable investments can change the ways food system innovations are developed and prioritized.